Rubidium spectroscopy at high-pressure buffer gas conditions: detailed balance in the optical interaction of an absorber coupled to a reservoir. (30th October 2018) - Christopoulos, Stavros; Moroshkin, Peter; Weller, Lars; Gerwers, Benedikt; Forge, Ralf; Ockenfels, Till; Vewinger, Frank; Weitz, Martin
Abstract: Optical spectroscopy of atoms and molecules is a field where one usually operates very far from thermal equilibrium conditions. A prominent example is spectroscopy of thin vapors, where the pump irradiation leads to a non-equilibrium distribution within the electronic structure that is well shielded from the environment. Here we describe experimental work investigating absorption and emission lines of rubidium vapor subject to a noble buffer gas environment with pressure 100–200 bar, a regime interpolating between usual gas phase and liquid/solid state conditions. Frequent elastic collisions in the dense buffer gas sample cause a large coupling to the environment. We give a detailed account of recent observations of the Kennard–Stepanov scaling, a Boltzmann-like thermodynamic frequency scaling between absorption and emission profiles, for both atomic and molecular rubidium species in the gaseous environment. Our observations are interpreted as due to the thermalization of alkali-noble gas submanifolds in both ground and electronically excited states respectively. Both pressure broadening and shift of the high pressure buffer gas D -lines system are determined. We also discuss some prospects, including possible advances in collisional laser cooling and optical thermometry.